Heaven official's blessing, manhua. Volume 1 - Moxiangtongxiu (Aloha Comics, 2024)
"Strange events have plagued Mount Yujun for many years: a mysterious demon has been abducting brides on their way to their weddings. At last, the Heavens have heard the prayers of the afflicted! Xie Lian, a god who has risen again after two demotions, is sent to aid the mortals and reclaim his status. However, finding himself on a mountain path, he encounters someone that he never anticipated..."--